A novel wear prediction model for planetary roller screw based on universal sliding distance model. (November 2022) - Xing, Mingcai; Zhang, Bohong; Deng, Pan; Xu, Jinquan; Cui, Yi
Abstract: This study proposes a wear prediction model for planetary roller screw based on universal sliding distance model. The sliding distance model is derived by coordinate transformation. Considering meshing and motion characteristics, the wear depth distribution in contact region, and accumulated wear depth of screw and roller are predicted. It is found that the maximum wear depth and sliding distance appear below the center of contact region, and the axial motion distance of roller has a considerable effect on accumulated wear depth distribution of screw. Furthermore, the effects of roller numbers, thread pitch, number of roller thread and axial load on wear depth of screw and roller are analyzed.